BOLA SHAXSINING KOGNITIV RIVOJLANISHIDA RAQAMLI TEXNOLOGIYALARNING TA’SIRI - Norbosheva, M.A. (SCIENCE and SOCIETY, 2023)
The article discusses foreign approaches to the study of the use of digital devices by preschoolers, comments on the possible advantages and dangers of the influence of digital technologies on the cognitive development of preschoolers.